INTEGRASI SISTEM MANAJEMEN MUTU TERPADU BERBASIS ISO DAN MAQASHID ASY-SYARI’AH DI LEMBAGA PENDIDIKAN ISLAM (LPI) - Bahruddin; Rhendica (STKIP Subang, 2026)
Islamic Educational Institutions (LPIs) face the global challenge of improving managerial efficiency while maintaining religious values. This article discusses the integration of Learning Management Systems (LMS) with ISO 9001, 14001, and 45001 standards, as well as the addition of ISO 37001 (Anti-Bribery) and ISO 27001 (Information Security) dimensions. The philosophical foundation used is Maqasid al-Shari'ah, the ethical framework that unites all these standards. This study aims to formulate an integration model between an internationally recognized (ISO)-based Quality Management System (QMS) and the Maqasid al-Shari'ah principles as an effort to improve governance quality at Islamic Educational Institutions (LPIs). While ISO certification is effective in ensuring administrative and operational efficiency, LPIs require a strong spiritual dimension to maintain their religious identity. This research uses a descriptive qualitative method with a literature review and content analysis approach. The results of the study indicate that the integration of ISO with the five pillars of Maqashid Asy-Syari’ah (Hifdz ad-Din, al-Nafs, al-’Aql, al-Nasl, al-Mal, and al-Bi’ah) is able to create an educational ecosystem that is not only superior academically and managerially, but also oriented towards the welfare of the people (maslahah). In this model, ISO plays a role as a technical instrument to achieve effectiveness (itqan), while Maqashid Asy-Syari’ah plays a role as a spirit and value guide in strategic decision-making. This finding implies the importance of LPI not only pursuing the fulfillment of ISO administrative documents, but also aligning these procedures with the objectives of protecting religion, life, mind, descendants, property and the environment in order to realize rahmatan lil ‘alamin.